2018
DOI: 10.32674/jis.v8i2.94
|View full text |Cite
|
Sign up to set email alerts
|

Influences on International Student Choice of Study Destination: Evidence from the United States

Abstract: Competition to attract international students continues to grow and understanding the factors that influence study destination choice is critical to the marketing efforts of nations, states, and institutions. This surveybased study of international students at Michigan State University demonstrates that they appear to choose the country in which to study, and/or the specific school, with less regard for school location. The most critical influences on their choices were expected quality of education, reputatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 26 publications
0
18
0
3
Order By: Relevance
“…A survey-based study by Nicholls (2018) demonstrated that international students appear to first choose the country and institution in which they want to study, rather than the actual location of the university within that country. Also important to the respondents in this study was the quality of education, the reputation and ranking of the institution and academic department, safety and security, and the cost and affordability of the program of study.…”
Section: Institutional Choice and Recommendationmentioning
confidence: 99%
“…A survey-based study by Nicholls (2018) demonstrated that international students appear to first choose the country and institution in which they want to study, rather than the actual location of the university within that country. Also important to the respondents in this study was the quality of education, the reputation and ranking of the institution and academic department, safety and security, and the cost and affordability of the program of study.…”
Section: Institutional Choice and Recommendationmentioning
confidence: 99%
“…Por lo que, como en todo proceso, las políticas europeas y de la UA requieren de revisiones, nuevos enfoques y mejoras. Por ejemplo en las cuantías de las becas, dado que son también un activo determinante a la hora de seleccionar el programa (Nicholls, 2018) y un factor discriminante para acceder a la movilidad (Cuzzocrea & Cairns, 2020). Así, resulta necesario adecuar las cantidades para favorecer que todo el alumnado, y no solo las familias con más recursos, puedan acceder a estas.…”
Section: Discusión Y Conclusiones Finalesunclassified
“…Todos ellos esenciales a la hora de seleccionar el destino como si de un viaje turístico se tratara. Así, las universidades son vendidas como una marca que debe estar presente en RRSS y promocionarse como un destino de ocio y diversión para el alumnado extranjero (Nicholls, 2018;Cuzzocrea & Cairns, 2020). Aunque esto no quita la necesidad de visibilizar las oportunidades de movilidad (Ramos, Sánchez, Saucedo, & Cortés, 2021) que las universidades ofrecen a su alumnado con portales web que ofrezcan información práctica (Eurydice, 2017; European Commission/EACEA/Eurydice, 2020).…”
Section: Introductionunclassified
“…Kvalitnú prácu sprostredkovateľov má zabezpečovať sieť 400 medzinárodných poradenských stredísk pre študentov Education USA vo viac ako 175 krajinách prevádzkovaná ministerstvom zahraničných vecí USA. (Findlay et al, 2017;Nicholls, 2018) Výskum univerzít v USA ukázal, že približne 78% respondentov uviedlo, že ich inštitúcie využívajú služby agentov. Počas pôsobenia prezidenta Donalda Trumpa je však hospodárstvo silne orientované na trh.…”
Section: |unclassified